The potential impacts of the EVFTA on Vietnam’s imports of dairy products from the EU: a SMART model analysis - Bui, Dui Linh; Nguyen , Lam Quynh Mai; Ahmed, Rizwan (Journal of International Economics and Management, 2021)
This study investigates the potential impacts of tariff elimination under the European Union - Vietnam Free Trade Agreement (EVFTA) on Vietnam’s imports of dairy products from the European Union market. The SMART model, which is a simulation tool under the WITS, is employed with support data from TrendEconomy and Trade Map Database, UNCTAD’s TRAINS, WTO’s IDB (Integrated Data Base), and Vietnam’s Ministry of Finance. The study examines two scenarios of Vietnam’s tariff reduction commitments under the EVFTA and the big picture vVietnam’s import value by product line and by European Union (EU) nations would increase insignificantly as the trade creation effect dominates the trade diversion. Additionally, the results indicate insignificant welfare gain for the consumers and potential revenue loss for the government. The study provides insights for Vietnam’s dairy industry and policymakers to fully grasp the possible benefits and losses under the EVFTA and implications for decision-making.